PENERAPAN MODEL PEMBELAJARAN EKSPOSITORI DALAM PENGEMBANGAN LESSON PLAN PADA MATERI KINGDOM MONERA DI SMA/MA - Fitri Widyaningrum; Achmad Ali Fikri (BIO-EDU: Jurnal Pendidikan Biologi, 2023)
Students have different characteristics in learning. This requires a teacher to expend all his abilities to carry out learning that can be accepted by all students and in accordance with the material being taught. One of the components in learning activities at school is the Lesson Plan. A teacher must use an appropriate Lesson Plan in learning activities so that teaching and learning activities run conducively and effectively. This study aims to develop a Lesson Plan with an expository learning model at the senior high school level or equivalent. This research is a Research and Development (RnD) based research conducted using the PPE method which consists of three stages, namely Planning, production and evaluating. Researchers conducted interviews with biology teachers in high schools, then prepared a Lesson Plan that was adjusted to the interview data. Then practice it directly to students. The implementation of the Lesson Plan that has been made by researchers reaches 83.75%. So it can be concluded that the lesson plan used by researchers is feasible to use. Keywords: Lesson Plan; expository; RnD; PPE